How is Sexual Education in the View of Islamic Psychology? - Uyun, Muhamad; Salsabila, Alfida; Fitriani, Fitriani (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
This article discussed sex education based on Islamic psychology, an essential aspect of healthy physical and psychological development. Islamic psychology emphasized that sex education included not only biological aspects but also spiritual and moral dimensions. Sex education in Islam aimed to cultivate responsible behavior, self-respect, respect for others, and the preservation of purity and honor. The article reviewed various scientific publications on sex education based on Islamic psychology, aiming to explore fundamental principles, appropriate teaching methods, the prevention of deviant sexual behavior, and the protection of individuals from the negative impacts of media and environments that contradicted Islamic values. The methods used in this article included literature searches on Google Scholar, Connected Papers, and Science Direct, focusing on topics such as sex education, the Islamic perspective on sex, and Islamic psychology's view on sexuality. The research results were expected to provide insights for developing a holistic sex education curriculum grounded in Islamic values. This article also served as a guide for parents, educators, and the community in educating the younger generation. The implications of this approach included the need for a comprehensive and integrative education curriculum, training for educators, and support from families and the community in implementing sex education according to Islamic principles. Sex education within the framework of Islamic psychology not only imparted knowledge but also shaped noble and responsible character.Artikel ini membahas pendidikan seksual berdasarkan psikologi Islam, aspek penting dalam perkembangan individu sehat secara fisik dan psikologis. Pandangan psikologi Islam menekankan bahwa pendidikan seksual tidak hanya mencakup aspek biologis, tetapi juga dimensi spiritual dan moral. Pendidikan seksual dalam Islam bertujuan membentuk perilaku bertanggung jawab, menghargai diri sendiri dan orang lain, serta menjaga kesucian dan kehormatan. Artikel ini mengkaji berbagai literatur ilmiah yang membahas pendidikan seksual berbasis psikologi Islam, dengan tujuan mengeksplorasi prinsip dasar, metode pengajaran yang sesuai, pencegahan perilaku seksual menyimpang, dan perlindungan individu dari dampak negatif media serta lingkungan yang bertentangan dengan nilai-nilai Islam. Metode yang digunakan dalam artikel ini meliputi penelusuran literatur dari Google Scholar, Connected Papers, dan Science Direct, dengan fokus pada topik pendidikan seksual, perspektif Islam terhadap seks, dan pandangan psikologi Islam terhadap seksualitas. Hasil penelitian diharapkan memberikan wawasan bagi pengembangan kurikulum pendidikan seksual holistik yang berlandaskan nilai-nilai Islam. Artikel ini juga menjadi panduan bagi orang tua, pendidik, dan masyarakat dalam mendidik generasi muda. Implikasi dari pendekatan ini mencakup perlunya kurikulum pendidikan yang komprehensif dan integratif, pelatihan bagi pendidik, serta dukungan keluarga dan masyarakat dalam menerapkan pendidikan seksual sesuai prinsip Islam. Pendidikan seksual dalam kerangka psikologi Islam tidak hanya memberikan pengetahuan, tetapi juga membentuk karakter luhur dan bertanggung jawab.